Characterization of Phytochemicals, Nutrients, and Antiradical Potential in Slim Amaranth - Umakanta Sarker; Shinya Oba; Walaa F. Alsanie; Ahmed Gaber (MDPI AG, 2022)
Slim amaranth (A. hybridus) having a C4 photosynthetic pathway with diverse variability is a climate-resilient crop that tolerates abiotic stresses. Owing to the high productivity of the C4 pathway, we have been searching for suitable accessions as preferable high-yielding antioxidant-enriched cultivars with ample bioactive compounds, or for future breeding programs to improve bioactive compounds as a source of natural antioxidants. Twelve slim amaranth accessions were tested for nutraceuticals, phytopigments, radical scavenging capacity (two different assays), vitamins, total flavonoids, and total polyphenols content. Slim amaranth leaves contained ample dietary fiber, protein, moisture, and carbohydrates. The current investigation demonstrated that there was remarkable K, Ca, Mg (8.86, 26.12, and 29.31), Fe, Mn, Cu, Zn, (1192.22, 275.42, 26.13, and 1069.93), TP, TF (201.36 and 135.70), pigments, such as chlorophyll a, ab, and b, (26.28, 38.02, and 11.72), betalains, betaxanthins, betacyanins (78.90, 39.36, 39.53,), vitamin C (1293.65), β-carotene, total carotenoids, (1242.25, 1641.07), and TA (DPPH, ABTS+) (27.58, 50.55) in slim amaranth leaves. The widespread variations were observed across the studied accessions. The slim amaranth accessions, AH11, AH10, and AH12, exhibited high profiles of antioxidants including high potentiality to quench radicals and can be selected as preferable high-yielding antioxidant-enriched cultivars with ample bioactive compounds. Phytopigments, flavonoids, vitamins, and phenolics of slim amaranth leaves showed intense activity of antioxidants. Slim amaranth could be a potential source of proximate phenolics, minerals, phytopigments, vitamins, and flavonoids for gaining adequate nutraceuticals, bioactive components, and potent antioxidants. Moderate yielding accessions having moderate phytochemicals can be used to develop new high-yielding antioxidant-enriched cultivars for future breeding programs to improve bioactive compounds as a source of natural antioxidants.